Agricultura familiar e as políticas públicas de crédito rural na Amazônia: uma revisão integrativa de literatura - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This article analyzes access to the National Program for Strengthening Family Farming (PRONAF) in the Brazilian Amazon. The methodology used was based on an integrative literature review, which provides a broad analysis of the literature on the topic, enabling discussions about the methods and results. In the Brazilian Amazon, PRONAF is underway with the inclusion of families working in agriculture; however, there are some issues regarding access to and management of resources from this public policy. One of the problems to be addressed, as highlighted by the review, is the lack of technical assistance to guide rural workers on sustainable land use, which could increase the duration of land use. This study highlights how public policies can contribute to the economic, social, and environmental development of the Amazon region.
Keywords: PRONAF; Amazônia; Revisão Integrativa da Literatura; Agricultura Familiar; CNPQ:: CIÊNCIAS AMBIENTAIS